Seedling emergence and growth of Quercus spp. following severe drought effects on a Pinus sylvestris canopy - Galiano, Lucía; Martínez-Vilalta, Jordi; Eugenio, Màrcia; Granzow-de la Cerda, Íñigo; Lloret, Francisco (Journal of Vegetation Science, 2012)
Questions We addressed the following questions: (1) did defoliation and die-off of the dominant Pinus sylvestris, induced by an extreme drought episode, favour emergence of other tree species; (2) did the defoliated canopies of P. sylvestris resulting from drought promote radial growth among other pre-existing tree species seedlings under them? Location P. sylvestris forest in Central Pyrenees (NE Spain) affected by a severe drought in 2004–2005. Methods Despite increased focus on climate-related forest die-off, studies of the effects on regeneration processes following extreme drought remain scarce. We analysed whether an episode of drought-induced mortality on the dominant P. sylvestris L. may act as a driver of vegetation shift. Seedlings of Quercus humilis Mill. and Q. ilex L. from 27 plots were sampled under P. sylvestris canopies with <50% and ≥50% defoliation (standing dead trees included) to determine age distribution and radial growth using a retrospective, dendrochronological approach. Results Drought-induced canopy losses appear not to be compensated by regeneration of P. sylvestris. Recruitment of below-canopy tree species (specifically Q. humilis and Q. ilex) that could potentially become dominant was high in the entire studied area. However, the spatial patterns of Quercus spp. regeneration following the 2004–2005 drought were complex. While the emergence of new Quercus spp. seedlings was reduced under open, drought-induced canopies, growth of seedlings already established was favoured in open-canopy conditions. Conclusions Although the effects of extreme drought events may disfavour the establishment of new recruits, enhanced growth responses of a pre-established seedling bank could still contribute to accelerate forest dynamics under drier conditions. Because of the predicted increases in intensity and frequency of extreme droughts, monitoring studies are key to elucidate whether the initial patterns observed will be maintained in the long term, eventually leading to a vegetation shift.
Keywords: Canopy gap; Extreme climatic episode; Pinus sylvestris; Quercus humilis; Quercus ilex; seedling growth; Seedling recruitment; tree mortality; Vegetation shift